As cooperativas de crédito rural solidárias como indutoras do desenvolvimento local - de Freitas, Alair Ferreira (2015)
The objective of this paper is to develop a conceptual analysis on operation of solidary rural credit unions, linked primarily to family agriculture and proposi-tions to induce local development processes. To build an analytical framework in order to understand this phenomenon, we started with the analyses and rela-tionships on the concepts of: (i) development and the notions that dispute its sig-nificance to introduce the concept of local development and their "new" refer-ences; (ii) the credit considered strategic factor in the induction of local devel-opment; (iii) credit unions as important instruments of operationalisation of credit; (iv) the desirability of governance while operationalisation of credit via the cooperative; (v) confidence; and (vi) social networks. These elements are ana-lysed while social mechanisms of governance in cooperatives, which do not ex-clude the formal institutional mechanisms, but will serve as addictive potential, in addition to contributing to reduce risk. The opportunity to conduct a finan-cial investment, made viable by the cooperative, creates economic conditions for farmers seize opportunities productive and constitute sustainable ventures. Thus, the expansion of the scope of cooperative allows credit accessed is invested and become a factor of induction of local development. This process fosters a virtuous cycle mediated by credit unions in places where they operate.